Obituary: in Memory of Otto Harsema (11 September 1939 - 8 September 2013) - Jaap Beuker (EXARC Journal)
On the 8th of September 2013 Drs. Otto Harm Harsema died from a bad fall during his stay in Poitiers (FR). Otto, born 11 September 1939 in Uithuizermeeden (NL), studied Social Geography and Prehistory at the Rijksuniversiteit Groningen. From 1967, he was employed by both the Provinciaal Museum van Drenthe in Assen (presently called the Drents Museum) and the Biologisch-Archaeologisch Instituut (BAI, the present GIA) at the Rijksuniversiteit Groningen.